+0

# Functions help

0
300
4

Function f ( x) = 3( x − 5)2 + 9 is transformed as follows.

1.  f(x) is shifted 6 units to right to obtain function g(x). What is the equation of g(x) in terms of f(x)?

2.  What is the equation of g(x) in terms of x?

3.  Then, g(x) is shifted 7 units down to obtain function j( x) . What is the equation of j(x) in terms of

f(x)?

4.  What is the equation of j(x) in terms of x?

Feb 8, 2018

#1
+1

f(x)  = 3 (x - 5)^2   + 9

1.  f(x) is shifted 6 units to right to obtain function g(x). What is the equation of g(x) in terms of f(x)?

g(x)  = f(x - 6)

2.  What is the equation of g(x) in terms of x?

g(x)  = 3 (x - 11)^2  +  9

3.  Then, g(x) is shifted 7 units down to obtain function j( x) . What is the equation of j(x) in terms of

f(x)?

j(x)  =  f(x - 6)  - 7

4.  What is the equation of j(x) in terms of x?

j(x)  = 3 (x - 11)^2  + 2

EDIT to correct a previious omission....   Feb 8, 2018
edited by CPhill  Feb 8, 2018
edited by CPhill  Feb 9, 2018
edited by CPhill  Feb 9, 2018
#2
0

I forgot to ask, can you show the steps you took to arrive at these answers?

Guest Feb 8, 2018
#3
+1

The steps are not too long-winded luckily. Unfortunately for Cphill, the 3 that precedes the argument is missing from Cphill's answer.

1) As Cphill mentioned, if \(f(x)\) is the original function, then \(f(x-6)\) translates the function 6 units rightward. The instructions specificially request for the answer with an equation of \(g(x)\) in terms of \(f(x)\)\(g(x)=f(x-6)\)

2) In the previous answer, we determined that \(g(x)=f(x-6)\), so we can use this information to solve for the current problem:

 \(g(x)=f(x-6)\\ f(x)=3(x-5)^2+9\) \(f(x)=3(x-5)^2+9\) \(f(x-6)=3[(x-6)-5]^2+9\) \(f(x-6)=3(x-11)^2+9\) \(g(x)=f(x-6)=3(x-11)^2+9\\ g(x)=3(x-11)^2+9\)

3) If \(g(x)\) is translated 7 units downward to obtain \(j(x)\), then \(g(x)-7=j(x)\). Of course, the question asks for the equation to be in terms of f(x):

 \(j(x)=g(x)-7\) Now, substitute g(x)=f(x-6). \(j(x)=f(x-6)-7\)

4) Find j(x) in terms of x:

 \(j(x)=g(x)-7\) We have determined previously that \(g(x)=3(x-11)^2+9\), so substitute that in. \(j(x)=[3(x-11)^2+9]-7\) Now, simplify. There is not much to do. \(j(x)=3(x-11)^2+2\)
TheXSquaredFactor  Feb 9, 2018
#4
0

Thanks for spotting my omission, X2   Feb 9, 2018